Engineering reactive clay systems by ground rubber replacement and polyacrylamide treatment - O'Kelly, Brendan (My University, 2019)
This study investigates the combined performance of ground rubber (GR), the additive, and polyacrylamide (PAM), the binder, as a sustainable solution towards ameliorating the inferior geotechnical attributes of an expansive clay. The first phase of the experimental program examined the effects of PAM concentration on the soil’s mechanical properties—consistency, sediment volume attributes, compactability, unconfined compressive strength (UCS), reactivity and microstructure features. The second phase investigated the effects of GR content, with and without the optimum PAM concentration. An increase in PAM beyond 0.2 g/L, the identified optimum concentration, caused the excess PAM to act as a lubricant rather than a flocculant. This feature facilitated reduced overall resistance to sliding of soil particles relative to each other, thereby adversely influencing the improvement in stress–strain–strength response achieved for ≤0.2 g/L PAM. This transitional mechanism was further verified by the consistency limits and sediment volume properties, both of which exhibited only minor variations beyond 0.2 g/L PAM. The greater the GR content, the higher the mobilized UCS up to 10% GR, beyond which the dominant GR-to-GR interaction (i.e., rubber-clustering) adversely influenced the stress–strain–strength response. Reduction in the soil’s swell–shrink capacity, however, was consistently in favor of higher GR contents. Addition of PAM to the GR-blended samples amended the soil aggregate–GR connection interface, thereby achieving further improvements in the soil’s UCS and volume change behaviors. A maximum GR content of 20%, paired with 0.2 g/L PAM, managed to satisfy a major decrease in the swell–shrink capacity while improving the strength-related features, and thus was deemed as the optimum choice.
PUBLISHED
Keywords: Expansive clay; Polyacrylamide; Ground rubber; Sediment volume; Unconfined compressive strength; Swell-shrink capacity; Rubber-clustering; Smart & Sustainable Planet; CLAY; Environmental Geotechnics; Geotechnical Engineering; Geotechnics; POLYACRYLAMIDE GELS; POLYMER; SOIL; SOIL MODIFICATION; Soil Mechanics; Soil Mechanics & Foundations; expansive clay; ground rubber; waste tyres